SOME OBSERVATIONS ON THE FINE STRUCTURE OF THE LATERAL LINE ORGAN OF THE JAPANESE SEA EEL LYNCOZYMBA NYSTROMI - Hama, Kiyoshi (The Rockefeller University Press, 1965)

(untitled)
The fine structure of the lateral line organ of the Japanese sea eel Lyncozymba nystromi has been studied with the electron microscope. The sensory epithelium of the lateral line organ consists of a cluster of two major types of cells, the sensory hair cells and the supporting cells. The sensory cell is a slender element with a flat upper surface provided with sensory hairs, Two different types of synapses are distinguished on the basal surface of the receptor cell. The first type is an ending without vesicles and the second type is an ending with many vesicles. These are presumed to correspond to the afferent and the efferent innervations of the lateral line organ. The fine structure of the supporting cells and the morphological relationship between the supporting cells and the receptor cells were observed. The possible functions of the supporting cells are as follows: (a) mechanical and metabolic support for the receptor cell; (b) isolation of the individual receptor cell; (c) mucous secretion and probably cupula formation; (d) glial function for the intraepithelial nerve fibers. Both myelinated and unmyelinated fibers were found in the lateral line nerve. The mode of penetration of these fibers into the epithelium was observed.